STUDY ON ANTIBACTERIAL EFFECT OF MEDLAR AND HAWTHORN COMPOUND EXTRACT IN VITRO - Niu, Yang; Nan, Yi; Yuan, Ling; Wang, Rong (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
This paper evaluated the antibacterial effect of medlar and hawthorn compound extract in vitro. Water extract method and ethanol extraction method was adopted to prepare the compound extracts, and disc diffusion method and improved test tube doubling dilution method were used to conduct the antibacterial test on the two common pathogenic bacteria, Staphylococcus aureus and Klebsiella pneumonia, in vitro. The results showed that medlar and hawthorn compound extract was moderately sensitive to Staphylococcus aureus, while its inhibiting effect on Klebsiella pneumoniae was particularly significant, moreover, the antibacterial effect of ethanol extract was better than water extract. Medlar and hawthorn compounds had good antibacterial effect on the two pathogenic bacteria.